2017
DOI: 10.36812/pag.2017231/222-30
|View full text |Cite
|
Sign up to set email alerts
|

Superação de dormência das sementes e desenvolvimento de plântulas de acácia amarela (Cassia ferruginea (Schrad) Schrad ex DC)

Abstract: A necessidade de se averiguar ocorrência de dormência em sementes de acácia amarela é importante para produção de mudas sadias e com desenvolvimento desejável, principalmente para recomposição florestal. O experimento foi realizado no IFES, com sementes extraídas manualmente de vagens recém-colhidas de plantas localizadas no instituto, as mesmas foram imersas em água destilada, solução de giberelina 0,3 % (v/v) e solução de cloreto de potássio 5 % (v/v), por 30 minutos, água quente (90 ºC) e água com gelo (ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Alves (2016), when testing different densities of Stylosanthes capitata and Stylosanthes macrocephala, found no differences in the density of native planted species. Dormancy-overcoming studies of Cassia ferruginea have revealed good germination results under controlled conditions (PAIXÃO et al, 2017;CRUZ et al, 2019). However, dos Santos et al (2009) obtained high mortality and low growth of this species after sowing in a controlled environment when testing different substrates compared to the other species studied.…”
Section: Discussionmentioning
confidence: 99%
“…Alves (2016), when testing different densities of Stylosanthes capitata and Stylosanthes macrocephala, found no differences in the density of native planted species. Dormancy-overcoming studies of Cassia ferruginea have revealed good germination results under controlled conditions (PAIXÃO et al, 2017;CRUZ et al, 2019). However, dos Santos et al (2009) obtained high mortality and low growth of this species after sowing in a controlled environment when testing different substrates compared to the other species studied.…”
Section: Discussionmentioning
confidence: 99%